2022
DOI: 10.1007/s12200-022-00007-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial beam reshaping and large-band nonlinear conversion in rectangular-core phosphate glass fibers

Abstract: Here we present the ability of Nd3+-doped zinc-phosphate glasses to be shaped into rectangular core fibers. At first, the physico-chemical properties of the developed P2O5-based materials are investigated for different concentrations of neodymium oxide and core and cladding glass compositions are selected for further fiber development. A modified stack-and-draw technique is used to produce multimode large rectangular-core optical fibers. Self-guided nonlinear effects acting as spatial beam reshaping processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…The issue includes five review articles and three research articles, covering topics from theory and modelling of fiber to novel fiber manufacturing and applications in optical modulation, sensing, energy conversion, wearables, etc. Strutynski et al [15] developed zinc-phosphate glasses doped with Nd 2 O 3 of different concentrations, and observed linear evolution of the glass properties with respect to the Nd 2 O 3 concentration. Based on that they produced multimode large rectangular-core fibers with a modified stack-and-draw method, and found that self-guided nonlinear effects acting as spatial beam reshaping processes in these newly-developed photonic structures led to the generation of spectral broadenings in the visible and near-infrared spectral domains.…”
mentioning
confidence: 99%
“…The issue includes five review articles and three research articles, covering topics from theory and modelling of fiber to novel fiber manufacturing and applications in optical modulation, sensing, energy conversion, wearables, etc. Strutynski et al [15] developed zinc-phosphate glasses doped with Nd 2 O 3 of different concentrations, and observed linear evolution of the glass properties with respect to the Nd 2 O 3 concentration. Based on that they produced multimode large rectangular-core fibers with a modified stack-and-draw method, and found that self-guided nonlinear effects acting as spatial beam reshaping processes in these newly-developed photonic structures led to the generation of spectral broadenings in the visible and near-infrared spectral domains.…”
mentioning
confidence: 99%